The Effectiveness of Using Mandarin Language in Optimizing Business and Marketing Strategies in Indonesia - Devi Alvionita Alindra (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2023)
The use of Mandarin language is an effective business strategy for marketing local products in the Chinese market. This is particularly relevant considering the presence of numerous foreign companies in Indonesia owned by Chinese investors. When targeting Chinese consumers, the use of Mandarin language becomes essential in conveying information and marketing products. Limited Mandarin language proficiency among marketing personnel can hinder the flow of information from external sources or provide information to customers. Therefore, a good understanding and proficiency in the Mandarin language become key factors in optimizing business and marketing strategies. This research employs a literature study method with the aim of understanding the role and influence of Mandarin language usage in optimizing business and marketing strategies. The population of this research includes individuals working in the business environment, particularly employees who utilize Mandarin language in their work.